Patient-Centered Care: An Opportunity to Accomplish the “Three Aims” of the National Quality Strategy in the Medicare ESRD Program - O’Hare, Ann M. (Clin J Am Soc Nephrol, 2014)
In light of mounting federal government debt and levels of Medicare spending that are widely viewed as unsustainable, commentators have called for a transformation of the United States health care system to deliver better care at lower costs. This article presents the priorities of the Coalition for Supportive Care of Kidney Patients for how clinicians might achieve this transformation for patients with advanced CKD and their families. The authors suspect that much of the high-intensity, high-cost care currently delivered to patients with advanced kidney disease may be unwanted and that the “Three Aims” put forth by the National Quality Strategy of better care for the individual, better health for populations, and reduced health care costs may be within reach for patients with CKD and ESRD. This work describes the coalition’s vision for a more patient-centered approach to the care of patients with kidney disease and argues for more concerted efforts to align their treatments with their goals, values, and preferences. Key priorities to achieve this vision include using improved prognostic models and decision science to help patients, their families, and their providers better understand what to expect in the future; engaging patients and their families in shared decision-making before the initiation of dialysis and during the course of dialysis treatment; and tailoring treatment strategies throughout the continuum of their care to address what matters most to individual patients.